CROSS OVER: A RELIABLE MANEUVER IN THE CONFIRMATION OF ATRIOVENTRICULAR NODAL REENTRANT TACHYCARDIA ABLATION - Shah, Bakhtawar; Saidullah, Shahab; Awan, Zahid Aslam (Journal of Ayub Medical College Abbottabad, 2017)
Background: Atrioventricular nodal re-entrant tachycardia (AVNRT) is still the most common presentation to our electrophysiology laboratory for ablation. The aim of this study is to document the confirmative value of cross over manoeuvre in successful AVNRT ablation. Methods: This study was conducted in Hayat Abad Medical complex Peshawar June 2006 to October 2015. In all patient with AVNRT, Dual-nodal pathway physiology confirmed by programmed atrial pacing of eight Tran with an extra beat by 10 millisecond (ms) decrement and at least Atrial HIS (A-H) interval prolongation of 50 ms. The dual pathway was further confirmed by cross over manoeuvre. Slow pathway potential identified and radiofrequency ablation (RFA) energy applied at 60 temperatures and 30 powers in Left Anterior Oblique (LAO) projection. Post ablation absence of cross over documented with and without isoproterenol and patient followed for any complication or recurrence. Results: Total 567 patients studied with mean age 36.56±12.16 and male to female ratio 1:1.4 with presentation of supra-ventricular tachycardia (SVT). Slow pathway was successfully modified and statistically no significant complication or recurrence documented. Conclusion: Failure to cross over reliably excludes any conduction over the slow pathway and so recurrence of AVNRT. Keywords: Atrioventricular nodal re-entrant tachycardia; AVNRT; Supra-ventricular tachycardia; SVT; Radiofrequency ablation; Dual nodal pathway; Physiology